Copper-magnesium alloy wire for high-voltage wiring harness of new energy automobile and preparation method of copper-magnesium alloy wire
By optimizing the composition and process flow of copper-magnesium alloy, high-strength and high-conductivity copper-magnesium alloy wire materials were prepared, which solved the problems of material performance imbalance and production complexity in the existing technology, and achieved high efficiency of high-voltage wire harness of new energy vehicles Materials solutions.
Patent Information
- Application Number
- CN202411417459.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-voltage wire harness materials are difficult to balance between mechanical and electrical properties. The traditional copper-magnesium alloy process is complex, has high energy consumption, is cost-effective, and is difficult to achieve large-scale production.
By optimizing the composition ratio of copper-magnesium alloy, adding Sn, Nb, Ce, Y, and La elements, and using power or medium frequency non-vacuum smelting, hot rolling, drawing and heat treatment processes, high-strength and high-conductivity copper-magnesium are prepared by using power or medium frequency non-vacuum smelting, hot rolling, drawing and heat treatment processes. Alloy wire materials and use copper-magnesium alloy waste for resource recycling.
The best balance between the mechanical properties and electrical properties of copper-magnesium alloy wire material is achieved, the process flow is simplified, the cost is reduced, and it is suitable for high-voltage wiring harnesses of new energy vehicles, with significant environmental and economic benefits.
Smart Images

Figure CN119287208A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nonferrous metal processing, and in particular to a copper-magnesium alloy wire for high-voltage wiring harnesses of new energy vehicles and a preparation method thereof. Background Art
[0002] As the core component of the automobile circuit, the automobile wiring harness is the "nervous system" that connects the various electrical components inside the car. It carries the task of transmitting current and signals to ensure the normal operation of various functions of the car. With the development of the new energy vehicle industry, higher requirements are put forward for the wiring harness materials used inside the car, especially the high-voltage wiring harness, which not only needs to have good electrical properties to ensure the efficiency and safety of power transmission, but also needs to have sufficient mechanical properties to resist various physical impacts that may be encountered during the operation of the vehicle.
[0003] At present, the commonly used high-voltage wire harness materials on the market mainly include pure copper wire and copper-based alloy wire with less alloying elements added. Although traditional pure copper has high electrical conductivity, its hardness is low, and it is easy to deform and wear in practical applications. There are certain limitations in the balance of conductivity, strength and corrosion resistance, which limits its application performance in high-voltage wire harnesses. In order to improve the strength of pure copper, alloying has become an effective means. By adding an appropriate amount of alloying elements, the strength of copper can be significantly improved while maintaining its excellent conductivity. However, the addition of alloying elements will also bring some negative effects. In the copper matrix, the introduction of alloying elements will produce impurity scattering, reduce the free path of electrons, and thus lead to a decrease in the conductivity of copper alloys. Therefore, although copper-based alloys with other metal elements added can improve hardness and strength to a certain extent, they are often accompanied by a decrease in electrical conductivity, which affects the power transmission efficiency of the wire harness and is also difficult to achieve a balance between mechanical and electrical properties. Therefore, when selecting alloying elements and their contents, it is necessary to comprehensively consider their effects on the conductivity and strength of copper alloys.
[0004] At present, Cu-Mg alloy is widely used in new energy vehicle wiring harness materials due to its good strength and conductivity, but the strengthening effect brought by the low magnesium content is limited. At the same time, the magnesium element is active and easy to burn, which makes production difficult, the processing technology is relatively complex, and the cost is high, which is not conducive to large-scale production. Traditional copper-magnesium alloy strips mainly use ingot casting, heating, hot rolling, milling, multi-pass cold rolling, multi-pass annealing, cleaning and other processes. The process is cumbersome, energy-intensive, and inefficient. In addition, the cold rolling process will also cause problems such as stress concentration, work hardening, and surface defects in the material. Summary of the invention
[0005] In order to solve the above problems and meet the market requirements for the performance and quality of high-voltage wire harnesses, the present invention provides a copper-magnesium alloy wire for high-voltage wire harnesses of new energy vehicles and a preparation method thereof. By optimizing the alloy component ratio and improving the production process, the mechanical properties of the material are significantly improved while ensuring good electrical properties, providing strong support for the sustainable development of the new energy vehicle industry.
[0006] On the one hand, the present invention provides a copper-magnesium alloy wire for a high-voltage wire harness of a new energy vehicle, which is composed of the following components by mass percentage: Mg 0.2-0.6%, Sn 0.05-0.3%, Nb 0.01-0.2%, Ce0.01-0.1%, Y0.01-0.1%, La 0.01-0.1%, and the rest is Cu.
[0007] Furthermore, the copper-magnesium alloy wire is made of a single metal or an alloy as raw material.
[0008] Preferably, the raw material of the copper-magnesium alloy wire comprises 10%-40% of new copper-magnesium alloy processing waste material, wherein the waste material is waste and scraps recovered during the copper-magnesium alloy processing production process.
[0009] Preferably, the raw materials of the copper-magnesium alloy wire further include electrolytic copper and new copper-magnesium master alloy material, wherein the content of Mg in the copper-magnesium master alloy is 10%.
[0010] Another aspect of the present invention is to provide a method for preparing copper-magnesium alloy wire for high-voltage wire harness of new energy vehicles, comprising a process of smelting→rolling→drawing→heat treatment→finished product drawing.
[0011] Furthermore, the smelting process is non-vacuum smelting by industrial frequency heating or medium frequency heating; the rolling process is hot rolling; and the drawing process is one-time drawing.
[0012] Furthermore, the non-vacuum smelting process comprises the following steps: (1) placing a formulated amount of electrolytic Cu raw material into a smelting furnace and raising the furnace temperature to 1200-1300°C; (2) after the raw material is completely melted, adding a formulated amount of Cu-Mg master alloy, electrolytic tin, metal niobium, metal cerium, metal yttrium, and metal lanthanum into the molten metal, and adding charcoal or flake graphite for covering to prevent the alloy from oxidizing during the smelting process; (3) performing sufficient stirring for 30-40 minutes to ensure uniform mixing of the alloy components; (4) after the stirring is completed, the alloy is allowed to stand for ≥20 minutes to allow the gas and impurities in the melt to float up and be removed, thereby further ensuring the uniformity of the components; (5) after standing, the alloy is continuously cast to ensure the continuity and quality stability of the ingot; and (6) after the casting is completed, the ingot is subjected to surface descaling treatment to remove the oxide layer on the surface of the ingot and improve the surface quality of the ingot.
[0013] Furthermore, in the step (5), the continuous casting pulling speed is 4-8 mm / s, the pulling stroke is 8-12 mm, the stop is 2.5 to 3.5 s, the reverse thrust speed is 2-4 mm / s, and the reverse thrust stroke is 2-4 mm; the strip outlet temperature is 300-380°C; and the vibration frequency of the casting crystallizer is 60-90 times / min.
[0014] Furthermore, the surface descaling treatment in step (6) is performed by mechanical descaling, and the surface of the alloy ingot is polished on a lathe.
[0015] Furthermore, during the hot rolling process, the heating temperature is 800-850° C., the holding time is 1-3 hours, and the total processing rate is 80-90%.
[0016] Furthermore, during the single drawing process, the drawing speed is 60-100 m / min, the pass processing rate is 14-16%, and the total processing rate is >80%; wherein, the single drawing is performed using a giant drawing machine, and the lubricant used for the single drawing is a water-based emulsion.
[0017] Furthermore, the heat treatment process adopts a vertical vacuum annealing furnace or a horizontal vacuum annealing furnace for annealing, the treatment temperature is 420-470°C, the insulation time is 1.5-4h, and the vacuum degree is greater than 5×10 -2 Pa.
[0018] Furthermore, during the finished product drawing process, the drawing speed is 120m-200m / min, the pass processing rate is 10-16%, and the total processing rate is >92%; wherein, the finished product drawing adopts a special finished product wire drawing machine for drawing operation, and the lubricant used for the finished product drawing is an oily lubricant.
[0019] The advantages of the present invention are:
[0020] 1. The present invention optimizes the composition and content of the copper-magnesium alloy by adding Sn, Nb, Ce, Y and La elements through microalloying, and obtains a copper-magnesium alloy wire with high strength and high conductivity comprehensive properties by appropriately adjusting the content of the components according to specific applications, thereby achieving an optimal balance between mechanical properties and electrical properties;
[0021] 2. The present invention successfully prepares high-strength and high-conductivity copper-magnesium alloy wire by optimizing key process parameters such as smelting, hot rolling, drawing and heat treatment. Compared with the prior art, the preparation method is simple to operate and has low cost. It is suitable for the preparation and application scenarios of copper-magnesium alloys that require high strength, high toughness and high dimensional stability. At the same time, by rationally utilizing magnesium-copper alloy waste, it realizes the effective recycling and reuse of resources, has significant environmental and economic benefits, and provides an ideal material solution for high-voltage wiring harnesses of new energy vehicles. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention is a preparation flow chart of a copper-magnesium alloy wire for a high-voltage wire harness of a new energy vehicle. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.
[0024] It should be noted that the various installation methods and technical terms mentioned in the invention are technical terms that have long been clearly known in the relevant technical field, so no further explanation is given. In addition, the same reference numerals are used for the same components, but this does not affect and should not constitute an accurate understanding of the technical solution by those skilled in the art.
[0025] Example 1
[0026] In this embodiment, the alloy is smelted using the following raw materials: magnesium-copper alloy waste and new materials (the new materials consist of electrolytic copper and copper-magnesium master alloy), electrolytic tin, metallic niobium, metallic cerium, metallic yttrium, and metallic lanthanum. The alloy composition is detailed in Table 1 below.
[0027] The specific preparation process is as follows:
[0028] 1. Melting: A horizontal continuous casting furnace is used for melting, and the heating method is industrial frequency heating.
[0029] (1) placing a formulated amount of electrolytic Cu raw material into a horizontal continuous casting furnace and raising the furnace temperature to 1250° C.
[0030] (2) After the metal is completely melted, 10% copper-magnesium alloy scrap, new copper-magnesium master alloy (Mg content is 10%), electrolytic tin, metal niobium, metal cerium, metal yttrium, and metal lanthanum are added to the molten metal, and then charcoal or flake graphite is added for covering;
[0031] (3) Stir thoroughly for 35 min;
[0032] (4) After stirring, the alloy was allowed to stand for 25 min;
[0033] (5) After standing, the alloy was continuously cast, and the casting process parameters were as follows: pulling speed of 8 mm / s, pulling stroke of 12 mm, stop of 3 s, reverse thrust speed of 2 mm / s, reverse thrust stroke of 3 mm, strip outlet temperature of 340°C, and vibration frequency of the crystallizer during the casting process of 75 times / min;
[0034] (6) After casting, the surface of the alloy ingot is polished on a lathe to perform surface descaling treatment.
[0035] 2. Hot rolling: heat the ingot to 825°C and keep it warm for 2 hours. Control the total hot rolling processing rate to 85%. After hot rolling, the ingot is also subjected to surface descaling by mechanical peeling.
[0036] 3. Single drawing: A giant drawing machine is used for single drawing, a water-based emulsion is used as the lubricant, the drawing speed is 80m / min, the pass processing rate is 15%, and the total processing rate is 80%.
[0037] 4. Heat treatment: vertical vacuum annealing furnace is used for annealing, and the vacuum degree is 5×10 -2 Pa. The heat treatment temperature is 450°C, the holding time is 2.5 hours, and the cooling method is natural cooling.
[0038] 5. Finished product drawing: Use a special finished product wire drawing machine for drawing operation, and use oil lubricant. The drawing speed is 150m / min, the pass processing rate is 13%, and the total processing rate must reach 92%.
[0039] The properties of the copper-magnesium alloy wire prepared by the method of Example 1 are shown in Table 2.
[0040] Example 2
[0041] The raw material composition of Example 2 is the same as that of Example 1, except that the content of the alloy components is different. The copper-magnesium alloy waste of Example 2 is 40%, as shown in Table 1 for details.
[0042] The preparation process of this embodiment 2 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0043] Step 1 During the smelting process: the heating method is medium frequency heating, the melting furnace temperature is 1300℃, the stirring time is 45min, and the alloy is left to stand for 20min. The casting process parameters are: the pulling speed is 7mm / s, the pulling stroke is 10mm, the stop is 3.5s, the reverse thrust speed is 3mm / s, the reverse thrust stroke is 4mm, the strip outlet temperature is 380℃, and the vibration frequency of the crystallizer is 90 times / min;
[0044] Step 2: During the hot rolling process: the hot rolling temperature is 850°C, the holding time is 2h, and the total hot rolling processing rate is 90%;
[0045] Step 3: During the first drawing process, the drawing speed is 70 m / min, the pass processing rate is 16%, and the total processing rate is 85%;
[0046] During the heat treatment process of step 4: the heat treatment temperature is 460°C and the holding time is 3h;
[0047] Step 5: During the finished product drawing process: the drawing speed is 200 m / min, the pass processing rate is 15%, and the total processing rate is 93%;
[0048] The properties of the copper-magnesium alloy wire prepared by the method of Example 2 are detailed in Table 2.
[0049] Example 3
[0050] The raw material composition of this embodiment 3 is the same as that of embodiment 1, except that the content of the alloy components is different, as shown in Table 1.
[0051] The preparation process of this embodiment 3 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0052] Step 1 During the melting process: the heating method is medium frequency heating, the melting furnace temperature is 1200℃, the stirring time is 30min, and the alloy is left to stand for 25min. The casting process parameters are: the pulling speed is 6mm / s, the pulling stroke is 9mm, the stop is 2.5s, the reverse thrust speed is 3.5mm / s, the reverse thrust stroke is 3mm, the strip outlet temperature is 320℃, and the vibration frequency of the crystallizer is 70 times / min;
[0053] Step 2: During the hot rolling process: the hot rolling temperature is 800°C, the holding time is 1h, and the total hot rolling processing rate is 80%;
[0054] Step 3: During the first drawing process, the drawing speed is 60 m / min, the pass processing rate is 15%, and the total processing rate is 80%;
[0055] During the heat treatment process of step 4: the heat treatment temperature is 430°C and the holding time is 1.5h;
[0056] Step 5: During the finished product drawing process: the drawing speed is 120 m / min, the pass processing rate is 14%, and the total processing rate is 92%;
[0057] The properties of the copper-magnesium alloy wire prepared by the method of Example 3 are detailed in Table 2.
[0058] Example 4
[0059] The raw material composition of this embodiment 4 is the same as that of embodiment 1, except that the content of the alloy components is different, as shown in Table 1.
[0060] The preparation process of this embodiment 4 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0061] Step 1 During the smelting process: the furnace temperature is 1250°C, the stirring time is 40 minutes, and the alloy is allowed to stand for 30 minutes. The casting process parameters are: the pulling speed is 4 mm / s, the pulling stroke is 8 mm, the stop is 3 seconds, the reverse thrust speed is 4 mm / s, the reverse thrust stroke is 4 mm, the strip outlet temperature is 360°C, and the vibration frequency of the crystallizer is 80 times / min;
[0062] Step 2: During the hot rolling process: the hot rolling temperature is 830°C, the holding time is 2.5h, and the total hot rolling processing rate is 85%;
[0063] Step 3: During the first drawing process, the drawing speed is 90 m / min, the pass processing rate is 15%, and the total processing rate is 85%;
[0064] During the heat treatment process of step 4: the heat treatment temperature is 460°C and the holding time is 3h;
[0065] Step 5: During the finished product drawing process: the drawing speed is 170 m / min, the pass processing rate is 14%, and the total processing rate is 92%;
[0066] The properties of the copper-magnesium alloy wire prepared by the method of Example 4 are detailed in Table 2.
[0067] Example 5
[0068] The raw material composition of this embodiment 5 is the same as that of embodiment 1, except that the content of the alloy components is different, as shown in Table 1.
[0069] The preparation process of this embodiment 5 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0070] Step 1 During the smelting process: the furnace temperature is 1270°C, the stirring time is 37 minutes, and the alloy is allowed to stand for 22 minutes. The casting process parameters are: the pulling speed is 6 mm / s, the pulling stroke is 10 mm, the stop is 3.2 seconds, the reverse thrust speed is 3.5 mm / s, the reverse thrust stroke is 3.5 mm, the strip outlet temperature is 300°C, and the vibration frequency of the crystallizer is 78 times / min;
[0071] Step 2: During the hot rolling process: the hot rolling temperature is 820°C, the holding time is 2h, and the total hot rolling processing rate is 84%;
[0072] In step 3, during the first drawing process, the drawing speed is 75 m / min, the pass processing rate is 16%, and the total processing rate is 82%;
[0073] During the heat treatment process of step 4: the heat treatment temperature is 440°C and the holding time is 4h;
[0074] Step 5: During the finished product drawing process: the drawing speed is 160 m / min, the pass processing rate is 12%, and the total processing rate is 94%;
[0075] The properties of the copper-magnesium alloy wire prepared by the method of Example 5 are detailed in Table 2.
[0076] Example 6
[0077] The raw material composition of this embodiment 6 is the same as that of embodiment 1, except that the content of the alloy components is different, as shown in Table 1.
[0078] The preparation process of this embodiment 6 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0079] Step 1 During the smelting process: the furnace temperature is 1220°C, the stirring time is 32 minutes, and the alloy is allowed to stand for 25 minutes. The casting process parameters are: the pulling speed is 8 mm / s, the pulling stroke is 10 mm, the stop is 2.7 seconds, the reverse thrust speed is 3 mm / s, the reverse thrust stroke is 3 mm, the strip outlet temperature is 310°C, and the vibration frequency of the crystallizer is 60 times / min;
[0080] Step 2: During the hot rolling process: the hot rolling temperature is 810°C, the holding time is 1.5h, and the total hot rolling processing rate is 86%;
[0081] Step 3: During the first drawing process, the drawing speed is 100 m / min, the pass processing rate is 14%, and the total processing rate is 80%;
[0082] During the heat treatment process of step 4: the heat treatment temperature is 430°C and the holding time is 2h;
[0083] Step 5: During the finished product drawing process: the drawing speed is 200 m / min, the pass processing rate is 11%, and the total processing rate is 95%;
[0084] The properties of the copper-magnesium alloy wire prepared by the method of Example 6 are detailed in Table 2.
[0085] Example 7
[0086] The raw material composition of this embodiment 7 is the same as that of embodiment 1, except that the content of the alloy components is different, as shown in Table 1.
[0087] The preparation process of this embodiment 7 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0088] Step 1 During the smelting process: the furnace temperature is 1280°C, the stirring time is 38 minutes, and the alloy is allowed to stand for 28 minutes. The casting process parameters are: the pulling speed is 6 mm / s, the pulling stroke is 8 mm, the stop is 3.3 seconds, the reverse thrust speed is 3.5 mm / s, the reverse thrust stroke is 3.5 mm, the strip outlet temperature is 370°C, and the vibration frequency of the crystallizer is 85 times / min;
[0089] Step 2: During the hot rolling process: the hot rolling temperature is 840°C, the holding time is 2.5h, and the total hot rolling processing rate is 87%;
[0090] In step 3, during the first drawing process, the drawing speed is 95 m / min, the pass processing rate is 15.5%, and the total processing rate is 83%;
[0091] During the heat treatment process of step 4: the heat treatment temperature is 450°C and the holding time is 3h;
[0092] Step 5: During the finished product drawing process: the drawing speed is 180 m / min, the pass processing rate is 17%, and the total processing rate is 92%;
[0093] The properties of the copper-magnesium alloy wire prepared by the method of Example 7 are detailed in Table 2.
[0094] Example 8
[0095] The raw material composition of this Example 8 is the same as that of Example 1, except that the content of the alloy components is different, as shown in Table 1 for details.
[0096] The preparation process of this embodiment 8 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0097] Step 1 During the smelting process: the furnace temperature is 1230°C, the stirring time is 35 minutes, and the alloy is allowed to stand for 20 minutes. The casting process parameters are: the pulling speed is 5 mm / s, the pulling stroke is 10 mm, the stop is 2.8 seconds, the reverse thrust speed is 2.8 mm / s, the reverse thrust stroke is 2.8 mm, the strip outlet temperature is 330°C, and the vibration frequency of the crystallizer is 72 times / min;
[0098] In step 2, during hot rolling: the hot rolling temperature is 820°C, the holding time is 2h, and the total hot rolling processing rate is 83%;
[0099] In step 3, during the first drawing process, the drawing speed is 80 m / min, the pass processing rate is 14.5%, and the total processing rate is 81%;
[0100] During the heat treatment process of step 4: the heat treatment temperature is 440°C and the holding time is 2.5h;
[0101] Step 5: During the finished product drawing process: the drawing speed is 160 m / min, the pass processing rate is 12%, and the total processing rate is 95%;
[0102] The properties of the copper-magnesium alloy wire prepared by the method of Example 8 are detailed in Table 2.
[0103] Example 9
[0104] The raw material composition of this embodiment 9 is the same as that of embodiment 1, except that the content of the alloy components is different, as shown in Table 1 for details.
[0105] The preparation process of this embodiment 9 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0106] Step 1 During the smelting process: the furnace temperature is 1240°C, the stirring time is 45 minutes, and the alloy is allowed to stand for 25 minutes. The casting process parameters are: the pulling speed is 5 mm / s, the pulling stroke is 10.2 mm, the stop is 3 seconds, the reverse thrust speed is 3.2 mm / s, the reverse thrust stroke is 3.2 mm, the strip outlet temperature is 340°C, and the vibration frequency of the crystallizer is 75 times / min;
[0107] Step 2: During the hot rolling process: the hot rolling temperature is 830°C, the holding time is 2.5h, and the total hot rolling processing rate is 85%;
[0108] In step 3, during the first drawing process, the drawing speed is 85 m / min, the pass processing rate is 15%, and the total processing rate is 82%;
[0109] During the heat treatment process of step 4: the heat treatment temperature is 470°C and the holding time is 2.5h;
[0110] Step 5: During the finished product drawing process: the drawing speed is 165 m / min, the pass processing rate is 13%, and the total processing rate is 92%;
[0111] The properties of the copper-magnesium alloy wire prepared by the method of Example 9 are detailed in Table 2.
[0112] Example 10
[0113] The raw material composition of this embodiment 10 is the same as that of embodiment 1, except that the content of the alloy components is different, as shown in Table 1 for details.
[0114] The preparation process of this embodiment 10 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0115] Step 1 During the smelting process: the furnace temperature is 1260°C, the stirring time is 40 minutes, and the alloy is allowed to stand for 25 minutes. The casting process parameters are: the pulling speed is 5 mm / s, the pulling stroke is 11 mm, the stop is 3.2 seconds, the reverse thrust speed is 3.5 mm / s, the reverse thrust stroke is 3.5 mm, the strip outlet temperature is 350°C, and the vibration frequency of the crystallizer is 78 times / min;
[0116] Step 2: During the hot rolling process: the hot rolling temperature is 840°C, the holding time is 2.5h, and the total hot rolling processing rate is 87%;
[0117] In step 3, during the first drawing process, the drawing speed is 90 m / min, the pass processing rate is 15%, and the total processing rate is 83%;
[0118] During the heat treatment process in step 4: the heat treatment temperature is 455°C and the holding time is 3h;
[0119] Step 5: During the finished product drawing process: the drawing speed is 170 m / min, the pass processing rate is 14%, and the total processing rate is 92%;
[0120] The properties of the copper-magnesium alloy wire prepared by the method of Example 10 are detailed in Table 2.
[0121] Embodiment 11
[0122] The raw material composition of this embodiment 11 is the same as that of embodiment 1, except that the content of the alloy components is different, as shown in Table 1 for details.
[0123] The preparation process of this embodiment 11 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0124] Step 1 During the smelting process: the furnace temperature is 1210°C, the stirring time is 32 minutes, and the alloy is allowed to stand for 25 minutes. The casting process parameters are: the pulling speed is 5 mm / s, the pulling stroke is 9 mm, the stop is 2.6 seconds, the reverse thrust speed is 2.5 mm / s, the reverse thrust stroke is 2.5 mm, the strip outlet temperature is 320°C, and the vibration frequency of the crystallizer is 68 times / min;
[0125] Step 2: During the hot rolling process: the hot rolling temperature is 810°C, the holding time is 1.5h, and the total hot rolling processing rate is 82%;
[0126] In step 3, during the first drawing process, the drawing speed is 75 m / min, the pass processing rate is 14%, and the total processing rate is 80%;
[0127] During the heat treatment process of step 4: the heat treatment temperature is 430°C and the holding time is 2h;
[0128] Step 5: During the finished product drawing process: the drawing speed is 140 m / min, the pass processing rate is 11%, and the total processing rate is 92%;
[0129] The properties of the copper-magnesium alloy wire prepared by the method of Example 11 are detailed in Table 2.
[0130] Example 12
[0131] The raw material composition of this embodiment 12 is the same as that of embodiment 1, except that the content of alloy components is different, as shown in Table 1 for details.
[0132] The preparation process of this embodiment 12 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0133] Step 1 During the smelting process: the furnace temperature is 1270°C, the stirring time is 38 minutes, and the alloy is allowed to stand for 28 minutes. The casting process parameters are: the pulling speed is 4 mm / s, the pulling stroke is 11.5 mm, the stop is 3.3 seconds, the reverse thrust speed is 3.5 mm / s, the reverse thrust stroke is 3.5 mm, the strip outlet temperature is 370°C, and the vibration frequency of the crystallizer is 85 times / min;
[0134] Step 2: During the hot rolling process: the hot rolling temperature is 840°C, the holding time is 2.5h, and the total hot rolling processing rate is 87%;
[0135] In step 3, during the first drawing process, the drawing speed is 95 m / min, the pass processing rate is 15.5%, and the total processing rate is 83%;
[0136] During the heat treatment process of step 4: the heat treatment temperature is 450°C and the holding time is 3h;
[0137] Step 5: During the finished product drawing process: the drawing speed is 180 m / min, the pass processing rate is 14%, and the total processing rate is 95%;
[0138] The properties of the copper-magnesium alloy wire prepared by the method of Example 12 are detailed in Table 2.
[0139] Example 13
[0140] The raw material composition of this embodiment 13 is the same as that of embodiment 1, except that the content of alloy components is different, as shown in Table 1 for details.
[0141] The preparation process of this embodiment 13 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0142] Step 1 During the smelting process: the furnace temperature is 1220°C, the stirring time is 33 minutes, and the alloy is allowed to stand for 23 minutes. The casting process parameters are: the pulling speed is 6 mm / s, the pulling stroke is 9.5 mm, the stop is 2.8 seconds, the reverse thrust speed is 2.8 mm / s, the reverse thrust stroke is 2.8 mm, the strip outlet temperature is 330°C, and the vibration frequency of the crystallizer is 72 times / min;
[0143] Step 2: During the hot rolling process: the hot rolling temperature is 820°C, the holding time is 2h, and the total hot rolling processing rate is 90%;
[0144] In step 3, during the first drawing process, the drawing speed is 80 m / min, the pass processing rate is 14.5%, and the total processing rate is 81%;
[0145] During the heat treatment process of step 4: the heat treatment temperature is 440°C and the holding time is 2.5h;
[0146] Step 5: During the finished product drawing process: the drawing speed is 160 m / min, the pass processing rate is 12%, and the total processing rate is 92%;
[0147] The properties of the copper-magnesium alloy wire prepared by the method of Example 13 are detailed in Table 2.
[0148] Embodiment 14
[0149] The raw material composition of this embodiment 14 is the same as that of embodiment 1, except that the content of alloy components is different, as shown in Table 1 for details.
[0150] The preparation process of this embodiment 14 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0151] Step 1 During the smelting process: the furnace temperature is 1230°C, the stirring time is 34 minutes, and the alloy is allowed to stand for 24 minutes. The casting process parameters are: the pulling speed is 6 mm / s, the pulling stroke is 10.2 mm, the stop is 3 seconds, the reverse thrust speed is 3.2 mm / s, the reverse thrust stroke is 3.2 mm, the strip outlet temperature is 340°C, and the vibration frequency of the crystallizer is 90 times / min;
[0152] Step 2: During the hot rolling process: the hot rolling temperature is 830°C, the holding time is 3h, and the total hot rolling processing rate is 80%;
[0153] In step 3, during the first drawing process, the drawing speed is 85 m / min, the pass processing rate is 15%, and the total processing rate is 82%;
[0154] During the heat treatment process of step 4: the heat treatment temperature is 470°C and the holding time is 2h;
[0155] Step 5: During the finished product drawing process: the drawing speed is 162 m / min, the pass processing rate is 13%, and the total processing rate is 92%;
[0156] The properties of the copper-magnesium alloy wire prepared by the method of Example 14 are detailed in Table 2.
[0157] Embodiment 15
[0158] The raw material composition of this embodiment 15 is the same as that of embodiment 1, except that the content of alloy components is different, as shown in Table 1 for details.
[0159] The preparation process of this embodiment 15 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0160] Step 1 During the smelting process: the furnace temperature is 1250°C, the stirring time is 35 minutes, and the alloy is allowed to stand for 25 minutes. The casting process parameters are: the pulling speed is 5 mm / s, the pulling stroke is 10 mm, the stop is 3.2 seconds, the reverse thrust speed is 3.5 mm / s, the reverse thrust stroke is 3.5 mm, the strip outlet temperature is 350°C, and the vibration frequency of the crystallizer is 78 times / min;
[0161] Step 2: During the hot rolling process: the hot rolling temperature is 840°C, the holding time is 2.5h, and the total hot rolling processing rate is 87%;
[0162] Step 3: During the first drawing process, the drawing speed is 90 m / min, the pass processing rate is 15%, and the total processing rate is 84%;
[0163] During the heat treatment process in step 4: the heat treatment temperature is 455°C and the holding time is 3h;
[0164] Step 5: During the finished product drawing process: the drawing speed is 170 m / min, the pass processing rate is 14%, and the total processing rate is 92%;
[0165] The properties of the copper-magnesium alloy wire prepared by the method of Example 15 are detailed in Table 2.
[0166] Example 16
[0167] The raw material composition of this Example 16 is the same as that of Example 1, except that the content of the alloy components is different, as shown in Table 1 for details.
[0168] The preparation process of this embodiment 16 is the same as that of embodiment 1, except that the process parameters involved in the preparation process are different:
[0169] Step 1 During the smelting process: the furnace temperature is 1200°C, the stirring time is 30 minutes, and the alloy is allowed to stand for 20 minutes. The casting process parameters are: the pulling speed is 4 mm / s, the pulling stroke is 8 mm, the stop is 2.2 seconds, the reverse thrust speed is 2 mm / s, the reverse thrust stroke is 2 mm, the strip outlet temperature is 310°C, and the vibration frequency of the crystallizer is 65 times / min;
[0170] Step 2: During the hot rolling process: the hot rolling temperature is 810°C, the holding time is 1h, and the total hot rolling processing rate is 80%;
[0171] In step 3, during the first drawing process, the drawing speed is 65 m / min, the pass processing rate is 14%, and the total processing rate is 80%;
[0172] During the heat treatment process in step 4: the heat treatment temperature is 420°C and the holding time is 4h;
[0173] Step 5: During the finished product drawing process: the drawing speed is 120 m / min, the pass processing rate is 10%, and the total processing rate is 92%;
[0174] The properties of the copper-magnesium alloy wire prepared by the method of Example 11 are detailed in Table 2.
[0175] Comparative Example 1
[0176] The preparation process and process parameters of this comparative example 1 are the same as those of Example 2, except that the alloy composition and content are different. Sn and Ce are not added to the alloy composition of this comparative example, as shown in Table 1 for details.
[0177] The properties of the copper-magnesium alloy wire prepared by the method of this comparative example 1 are shown in Table 2.
[0178] Comparative Example 2
[0179] The preparation process and process parameters of this comparative example 2 are the same as those of Example 2, except that the alloy composition and content are different. Ce, La and Y are not added to the alloy composition of this comparative example, as shown in Table 1 for details.
[0180] The properties of the copper-magnesium alloy wire prepared by the method of this comparative example 2 are shown in Table 2.
[0181] Comparative Example 3
[0182] The raw material composition and content of this comparative example 3 are the same as those of Example 2, except that the preparation process and process parameters are different. The strip outlet temperature of this comparative example during the casting process is 290°C.
[0183] The properties of the copper-magnesium alloy wire prepared by the method of this comparative example 3 are shown in Table 2.
[0184] Comparative Example 4
[0185] The raw material composition and content of this comparative example 4 are the same as those of Example 2, except that the preparation process and process parameters are different. In this comparative example, during the hot rolling process in step 2: the hot rolling temperature is 600°C, the holding time is 2h, and the total hot rolling processing rate is 82%.
[0186] The properties of the copper-magnesium alloy wire prepared by the method of this comparative example 4 are shown in Table 2.
[0187] Comparative Example 5
[0188] The raw material composition and content of this comparative example 5 are the same as those of Example 2, except that the preparation process and process parameters are different. In this comparative example, during the first drawing process in step 3: the drawing speed is 110 m / min, the pass processing rate is 20%, and the total processing rate is 90%.
[0189] The properties of the copper-magnesium alloy wire prepared by the method of this comparative example 5 are shown in Table 2.
[0190] Comparative Example 6
[0191] The raw material composition and content of this comparative example 6 are the same as those of Example 2, except that the preparation process and process parameters are different. In this comparative example, during the heat treatment process in step 4: the heat treatment temperature is 550° C., and the holding time is 2 h;
[0192] The properties of the copper-magnesium alloy wire prepared by the method of this comparative example 6 are detailed in Table 2.
[0193] Table 1 Alloy composition formula of copper-magnesium alloy wire
[0194]
[0195]
[0196] Table 2 Performance test table of copper-magnesium alloy wire
[0197]
[0198]
[0199] From the data in Table 2, we can see that:
[0200] Example 4 The copper-magnesium alloy wire prepared with relatively high magnesium content (0.6%) and relatively low content of other elements (Sn, Nb, Ce, Y, La are all between 0.01-0.05%) shows the best tensile strength (749MPa), Vickers hardness (238HV) and yield strength (714MPa), which shows that high magnesium content plays a key role in enhancing strength and hardness. However, it shows relatively low elongation (8.2%) and conductivity (65.0%), indicating that at high magnesium content, the ductility and conductivity of the material are reduced.
[0201] Relatively speaking, the content of magnesium and tin in Example 1 is relatively low (both are 0.20%), and the content of other elements is also relatively low (Nb, Ce, Y, La are all between 0.01% and 0.05%). The copper-magnesium alloy wire prepared with this alloy composition combination has excellent performance in elongation (10.2%) and conductivity (69.5%), indicating that low magnesium and low tin content help to improve the ductility and conductivity of the material. However, its tensile strength (705MPa), Vickers hardness (213HV) and yield strength (672MPa) have decreased. This shows that it is difficult to achieve a balance between the mechanical properties and electrical properties of the material, and the content of the components of the alloy will have a relative impact, limiting its applicability in high-strength applications.
[0202] The magnesium content of Example 2 and Example 5 is 0.35% and 0.40% respectively, the tin content is 0.15% and 0.10% respectively, and the contents of other elements (Nb, Ce, Y, La) are similar. These alloys show higher tensile strength (720MPa and 723MPa) and higher electrical conductivity (68.5% and 68.0%), and the elongation is also maintained at a moderate level (9.4%). The wire made of this alloy composition combination has the advantage of balanced mechanical properties and electrical properties.
[0203] The composition of Example 16 includes 0.40% magnesium and 0.10% tin, as well as 0.10% niobium and 0.05% cerium. This alloy composition combination performs well in terms of electrical conductivity (68.0%) and elongation (10.0%), while maintaining high hardness (216HV) and strength (712MPa), achieving a balance between electrical and mechanical properties, which indicates that within a certain range, moderately increasing the content of niobium and cerium can improve electrical conductivity and ductility without significantly reducing other properties.
[0204] The magnesium content of Example 6 is 0.80%, the tin content is 0.01%, and the rest is 0.01% niobium, 0.01% cerium, 0.01% yttrium, 0.1% lanthanum and the balance Cu; this alloy component combination performs well in tensile strength (815MPa), Vickers hardness (254HV) and yield strength (780MPa), but performs poorly in electrical conductivity, with a conductivity of only 54.4%, indicating that when the magnesium content is too high, the conductivity of the material will decrease.
[0205] The magnesium content of Example 8 is 0.10%, the tin content is 0.5%, and the rest are 0.01% niobium, 0.01% cerium, 0.01% yttrium, 0.01% lanthanum and the balance Cu; the mechanical and electrical properties of this alloy component combination are not good, and show an overall downward trend.
[0206] The results of Example 6 and Example 8 show that when the Mg content of the alloy component exceeds 0.6% or is less than 0.2%, and the Sn content exceeds 0.3% or is less than 0.05%, it will affect the performance of the copper-magnesium alloy wire, affecting the balance between its mechanical properties and electrical properties, and at the same time affecting the excellence of its overall performance.
[0207] However, Sn and Ce elements were not added to the copper-magnesium alloy of Comparative Example 1, and the obtained copper-magnesium alloy wire had poor mechanical properties such as tensile strength and Vickers hardness. Ce, Y and La elements were not added to the copper-magnesium alloy of Comparative Example 2, and the obtained copper-magnesium alloy wire had poor comprehensive mechanical and electrical properties including tensile strength, Vickers hardness and conductivity, indicating that the composition of the alloy will affect the performance of the copper-magnesium alloy wire.
[0208] At the same time, the results of Examples 3, 4, and 5 show that the preparation process of the copper-magnesium alloy wire affects its final performance. Among them, the tensile strength, Vickers hardness and other mechanical properties of Example 3 are poor, indicating that the low outlet temperature of the strip during the casting process will cause stress concentration and material deformation, affect the quality of the ingot and subsequent processing, and cause the comprehensive performance of the wire to deteriorate. At the same time, the outlet temperature of the strip should not be too high, which may affect the grain growth of the alloy. Therefore, the outlet temperature of the strip needs to be strictly controlled by adjusting the cooling rate, casting speed or cooling medium.
[0209] Compared with Example 2, the mechanical properties of Comparative Example 4, such as tensile strength and Vickers hardness, are not high, indicating that the temperature, time and total processing rate during the hot rolling process will affect the comprehensive properties of the material.
[0210] Compared with Example 2, the elongation of Comparative Example 5 is not high, indicating that the pass processing rate of a drawing is a key parameter affecting the quality of the wire, which directly affects the deformation degree and stress distribution of the wire after each drawing, and further affects the organizational uniformity and mechanical properties of the wire.
[0211] Compared with Example 2, the mechanical properties of Comparative Example 6, such as tensile strength and Vickers hardness, are not high, indicating that the temperature and time of heat treatment will affect the mechanical properties of the material.
[0212] The temperature and time of heat treatment are crucial to eliminating the internal stress of the wire and optimizing its structure. Too high a temperature will reduce the strength of the material, while too low a temperature will lead to insufficient toughness. Too long a holding time will soften the material, while too short a holding time will not completely eliminate the internal stress, increasing the difficulty of subsequent processing.
[0213] In summary, according to the performance test results of the embodiments and comparative examples in Table 2, it can be seen that the composition, content and preparation process of the alloy all affect the balance of mechanical properties and electrical properties of the copper-magnesium alloy wire. Through a comprehensive analysis of the alloy composition and performance data, the optimal alloy combination can be selected according to the specific application requirements to further achieve the best balance between performance and cost. Among them, Example 4 is suitable for applications requiring high strength and hardness, thanks to its high magnesium content; Example 1 is suitable for applications requiring high conductivity and ductility, thanks to its lower magnesium and tin content; Example 2, Example 5 and Example 16 are excellent choices for comprehensive performance, and through appropriate component allocation, a dual balance of mechanical properties and electrical properties is achieved.
[0214] At the same time, parameter conditions need to be strictly controlled during the preparation process to obtain copper-magnesium alloy wire with excellent performance.
[0215] For those skilled in the art, the invention is not limited to the details of the above exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic characteristics of the invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the invention is defined by the appended claims rather than the above description, so it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any reference numerals in the claims should not be regarded as limiting the claims involved.
[0216] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any minor modifications, equivalent substitutions and improvements made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.
Claims
1. A copper-magnesium alloy wire for high-voltage wire harness of new energy vehicles, characterized in that: The invention is composed of the following components by mass percentage: Mg 0.2-0.6%, Sn 0.05-0.3%, Nb 0.01-0.2%, Ce 0.01-0.1%, Y 0.01-0.1%, La 0.01-0.1%, and the rest is Cu.
2. The copper-magnesium alloy wire for high-voltage wire harness of new energy vehicles according to claim 1 is made of metal single substance or alloy as raw material, characterized in that: The raw material of the copper-magnesium alloy wire material contains 10%-40% of copper-magnesium alloy processing waste, wherein the waste is waste and scraps recovered during the copper-magnesium alloy processing and production process.
3. The copper-magnesium alloy wire for high-voltage wire harness of new energy vehicles according to claim 2, characterized in that: The raw materials of the copper-magnesium alloy wire also include electrolytic copper and new materials of copper-magnesium master alloy, wherein the content of Mg in the copper-magnesium master alloy is 10%.
4. A method for preparing a copper-magnesium alloy wire for a high-voltage wire harness of a new energy vehicle according to any one of claims 1 to 3, comprising a smelting → rolling → drawing → heat treatment → finished product drawing process, characterized in that: The smelting process is non-vacuum smelting by industrial frequency heating or medium frequency heating; the rolling process is hot rolling; and the drawing process is one-time drawing.
5. The method for preparing a copper-magnesium alloy wire for a high-voltage wire harness for new energy vehicles according to claim 4, characterized in that: The non-vacuum melting process comprises the following steps: (1) placing a formulated amount of electrolytic Cu raw material into a melting furnace and raising the furnace temperature to 1200-1300° C.; (2) after the raw material is completely melted, adding a formulated amount of Cu-Mg master alloy, electrolytic tin, metal niobium, metal cerium, metal yttrium, and metal lanthanum into the molten metal, and adding charcoal or flake graphite for covering; (3) stirring the molten metal sufficiently for 30-40 minutes to ensure uniform mixing of the alloy components; (4) after stirring, allowing the alloy to stand for ≥20 minutes; (5) after standing, continuously casting the alloy; and (6) after casting, performing surface descaling treatment on the ingot.
6. The method for preparing a copper-magnesium alloy wire for a high-voltage wire harness for a new energy vehicle according to claim 5, characterized in that: In the step (5), the continuous casting pulling speed is 4-8 mm / s, the pulling stroke is 8-12 mm, the stop is 2.5-3.5 s, the reverse thrust speed is 2-4 mm / s, and the reverse thrust stroke is 2-4 mm; the strip outlet temperature is 300-380°C; and the vibration frequency of the casting crystallizer is 60-90 times / min.
7. The method for preparing a copper-magnesium alloy wire for a high-voltage wire harness for a new energy vehicle according to claim 4, characterized in that: During the hot rolling process, the heating temperature is 800-850° C., the holding time is 1-3 hours, and the total processing rate is 80-90%.
8. The method for preparing a copper-magnesium alloy wire for a high-voltage wire harness for new energy vehicles according to claim 4, characterized in that: During the one-time drawing process, the drawing speed is 60-100 m / min, the pass processing rate is 14-16%, and the total processing rate is greater than 80%; wherein, the one-time drawing is performed using a giant drawing machine, and the lubricant used for the one-time drawing is a water-based emulsion.
9. The method for preparing a copper-magnesium alloy wire for a high-voltage wire harness for new energy vehicles according to claim 4, characterized in that: The heat treatment process adopts a vertical vacuum annealing furnace or a horizontal vacuum annealing furnace for annealing treatment, the treatment temperature is 420-470°C, the insulation time is 1.5-4h, the vacuum degree is> 5×10 -2 Pa.
10. The method for preparing a copper-magnesium alloy wire for a high-voltage wire harness of a new energy vehicle according to claim 4, characterized in that: During the finished product drawing process, the drawing speed is 120m-200m / min, the pass processing rate is 10-16%, and the total processing rate is greater than 92%; wherein, the finished product drawing adopts a special finished product wire drawing machine for drawing operation, and the lubricant used for the finished product drawing is an oily lubricant.
Citation Information
Patent Citations
High-strength high-conductivity electrical copper alloy and processing method thereof
CN106282645A
Rare earth-copper alloy wire for railway electric power continuous lines, and preparation method thereof
CN108220665A
High-strength bending-resistant copper alloy dropper wire and preparation method thereof
CN113174510A
Triple copper alloy for making high-strength conductive devices
CN1752244A
High-tensile conductive copper alloy excellent in stretchability and bendability and its production
JP1996209269A